Statutory Obligations Incurred by Occupational Health and Safety Law in Printing Industry and Press Sector - Yenidoğan, Semiha; Çırakoğlu, Sevil ([TR] Akademik Bilişim Araştırmaları Derneği, 2019)
Printing industry is a sector requiring extensive examination in terms of occupational health and safety due to being a line of work having hazardous chemical used therein, requiring transport of heavy loads, having intensive electrical energy, and having movable cylinder and sharp objects use. The fact that negative conditions containing risky activities in terms of human health are present in the printing industry and press sector increases the importance of occupational health and safety. According to Annex-1 in the Notification of Workplace Hazard Classes Relating to Occupational Health and Safety published in the Official Gazette dated 26.12.2012, it is within the class of hazardous workplace. Thus, occupational health and safety in the printing industry and press sector worth and required an extensive evaluation. In this article, evaluation of printing industry and press sector in terms of occupational health and safety was carried out and statutory obligation was examined. Firstly, general features of the printing industry and press sector were briefly mentioned, afterwards works and risks, occupational accidents and occupational diseases in the printing industry and press sector were handled with various dimensions thereof. The sector was evaluated with its dimension of occupational health and safety thereof.

Basım Endüstrisi tehlikeli kimyasalların kullanıldığı, ağır yüklerin taşınmasını gerektiren, elektrik enerjisinin yoğun olduğu, hareketli silindir ve kesici makinelerin kullanıldığı bir iş kolu olduğundan iş sağlığı ve güvenliği açısından geniş kapsamlı incelenmesi gereken bir sektördür. İnsan sağlığı açısından riskli faaliyetler içeren olumsuz koşullar basım sanayi ve matbaa sektöründe de olması sebebi ile iş sağlığı ve güvenliğinin de önemini arttırmaktadır. 26.12.2012 tarihli Resmi Gazetede yayınlanan İş Sağlığı ve Güvenliğine İlişkin İş yeri Tehlike Sınıfları Tebliğindeki Ek-1’e göre tehlikeli iş yeri sınıfında yer almaktadır. Bu durumunda basım sanayi ve matbaa sektöründe iş sağlığı ve güvenliği konusunda geniş bir değerlendirmeyi hak etmekte ve gerekli kılmaktadır. Bu makalede, basım sanayi ve matbaa sektörünün iş sağlığı ve güvenliği bakımından bir değerlendirmesi yapılmış ve yasal zorunluluklar incelenmiştir. Öncelikli olarak basım sanayi ve matbaa sektörünün genel özelliklerine kısaca değinilmiş daha sonra, basım sanayi ve matbaa sektöründeki işler ve riskler, iş kazaları ve meslek hastalıkları çeşitli boyutlarıyla ele alınmıştır. Sektör iş sağlığı ve güvenliği boyutuyla değerlendirilmiştir.
Basım Sanayi ve Matbaa Sektöründe İş Sağlığı ve Güvenliği Kanununun Getirdiği Yasal Zorunluluklar